Nevirapine-Based Antiretroviral Therapy Impacts Artesunate and Dihydroartemisinin Disposition in HIV-Infected Nigerian Adults. (5th March 2012) - Fehintola, Fatai A.; Scarsi, Kimberly K.; Ma, Qing; Parikh, Sunil; Morse, Gene D.; Taiwo, Babafemi; Akinola, Ibrahim Tope; Adewole, Isaac F.; Lindegardh, Niklas; Phakderaj, Aphiradee; Ojengbede, Oladosu; Murphy, Robert L.; et al.
Abstract : Background . Nevirapine- (NVP-) based antiretroviral therapy (ART) and artesunate-amodiaquine are frequently coprescribed in areas of HIV and malaria endemicity. We explored the impact of this practice on artesunate and dihydroartemisinin pharmacokinetics. Methods . We conducted a parallel-group pharmacokinetic comparison between HIV-infected patients receiving NVP-based ART (n = 10 ) and ART-naive controls (n = 11 ). Artesunate-amodiaquine 200/600 mg was given daily for three days. Measurement of drug concentrations occurred between 0 and 96 hours after the final dose. Pharmacokinetic parameters were determined using noncompartmental analysis. Results . Comparing the NVP group to controls, clearance of artesunate was reduced 50% (1950 versus 2995 L/h; P = 0.03 ), resulting in a 45% increase in the AUC0-96 (105 versus 69 ug ∗ hr/L; P = 0.02 ). The half-life of dihydroartemisinin was shorter in the NVP group (1.6 versuss 3.2 h; P = 0.004 ), but other dihydroartemisinin pharmacokinetic parameters were unchanged. A lower conversion of artesunate to dihydroartemisinin was observed in the NVP group (dihydroartemisinin: artesunate AUC0-96 = 5.6 versuss 8.5 in NVP and control groups, respectively, P = 0.008 ). Conclusion . Although NVP-containing ART impacted some pharmacokinetic parameters of artesunate and dihydroartemisinin, overall exposure was similar or better in the NVP group.